Zmiana priorytetów domowej ekonomii w świetle kryzysu ekologicznego. Nowe ekologiczno-edukacyjne wyzwania dla rodziny = A change in the priorities of home economics in the light of the environmental crisis. New ecological and educational challenges for the family - Wachowiak, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The themes of responsibility and care for the environment in the local dimension and in everyday life are present in the literature and indicate that the slogan of sustainable development is very much up-to-date. The importance of local communities in this area of activity is growing. They are characterised by a genuine concern for the environment, unlike the one centrally controlled by the state. The idea of sustainable development presented in the article is part of the activities undertaken by the International Federation for Home Economics.
Keywords: domowa ekonomia; edukacja ekologiczna dla domowej ekonomii; jakość życia; zrównoważony rozwój; home economics; environmental education for home economics; quality of life; sustainable development